Assessing the Quality of Decision Making in the Development and Regulatory Review of Medicines: Identifying Biases and Best Practices. (March 2017) - Bujar, Magdalena; Donelan, Ronan; McAuslane, Neil; Walker, Stuart; Salek, Sam
Background: Although the quality of decision making (QDM) in the development and regulatory review of medicines influences the delivery of new products, there appears to be no suitable instrument to assess QDM in this area. The aim of this study was to assess differences in QDM using a validated instrument, the Quality of Decision-Making Orientation Scheme (QoDoS), to identify best practices and biases affecting individuals and their organization, as well as to assess differences in decision-making behaviors between pharmaceutical companies and regulatory agencies. QoDoS also enables the measurement against 10 quality decision-making practices (QDMPs) that underpin a quality process. Methods: QoDoS, consisting of 47 items that assess individual and organizational decision-making approaches and influences, was completed by 76 participants from regulatory agencies and pharmaceutical companies. Results: Having a systematic, structured approach to aid in decision making is achieved to a greater extent at an individual level (72%) compared with that of the organization (38%). Key differences between company and agency decision making were uncovered. While it was recognized that both stakeholders felt that their decision making could be improved (100% agencies; 92% companies), training in the science of decision making was rarely provided. Conclusions: QoDoS has the ability to measure differences in QDM between individuals and organizations within companies and agencies. The benefits of assessing QDMPs with QoDoS include enabling an increased awareness of biases and best practices that should be incorporated into a decision-making framework; increasing productivity and reducing uncertainty around decision making, thereby resulting in more predictable outcomes for organizations. In addition, it provides a basis for discussion of the issues in decision making within an organization as well as between stakeholders to encourage a level of partnership. Finally, measurements of QDM will enable trust, consistency, transparency, and timeliness to be built into critical decisions that affect medicines' availability.